2018
DOI: 10.3389/fimmu.2018.02952
|View full text |Cite
|
Sign up to set email alerts
|

Innate Anti-microbial and Anti-chemotaxis Properties of Progranulin in an Acute Otitis Media Mouse Model

Abstract: Acute otitis media (AOM) is one of the most common infectious diseases primarily caused by Streptococcus pneumoniae (S.pn) among children. Progranulin (PGRN) is a multifunctional growth factor widely expressed in various tissues and cells. Studies have confirmed that PGRN is involved in the development of a variety of inflammatory diseases. We found that the expression of PGRN increased significantly in the middle ear of wild mice with AOM. However, its physiological functions in AOM still remain unknown. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Additionally, Wang et al . [ 41 ] reported an enhanced recruitment of live macrophages with the decreased bacterial clearance, impaired endocytosis capacity of macrophages accompanied with Progranulin (PGRN) deficiency and finally, Cronk et al . [ 42 ] reported on the differential gene expression profile on live Mecp2-null peritoneal macrophages implying a key role of this gene in sustaining macrophage function [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Wang et al . [ 41 ] reported an enhanced recruitment of live macrophages with the decreased bacterial clearance, impaired endocytosis capacity of macrophages accompanied with Progranulin (PGRN) deficiency and finally, Cronk et al . [ 42 ] reported on the differential gene expression profile on live Mecp2-null peritoneal macrophages implying a key role of this gene in sustaining macrophage function [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Side by side comparison of all live end stage macrophages cultures derived from SNCA A53T iPSC, GRN R493X iPSC, and MECP2 HM iPSC revealed a strong impairment of phagocytic function when compared to live end stage parental iPSC derived macrophages (S4 Fig) . This observation supports data published by Haenseler et al [14] on the impairment in phagocytic functions in live iPSC-derived macrophages from PD patients with SNCA Triplication and A53T mutations. Additionally, Wang et al [41] reported an enhanced recruitment of live macrophages with the decreased bacterial clearance, impaired endocytosis capacity of macrophages accompanied with Progranulin (PGRN) deficiency and finally, Cronk et al [42] reported on the differential gene expression profile on live Mecp2-null peritoneal macrophages implying a key role of this gene in sustaining macrophage function [42].…”
Section: Phagocytic Function Of Macrophages Is Retained Pre and Post Cryopreservationmentioning
confidence: 99%
“…PGRN is a necessary secretory cofactor to enhance the driving response of TLR 9 to CpG-ODNs. As a key soluble cofactor in TLR 9 signal transduction, PGRN is related to innate immunity [ 85 - 89 ].…”
Section: Othersmentioning
confidence: 99%
“…Recently, Wang et al found a multifunctional growth factor, Progranulin (PGRN), was involved in AOM in an unusual way in the study of PGRN-deficient (PGRN -/-) mouse model (Wang et al, 2018). After Spn inoculation, PGRN -/mice exhibited increased macrophage recruitment in ME but delayed bacteria clearance.…”
Section: Genes Involved In Anti-inflammatory Responses In Ommentioning
confidence: 99%
“…After Spn inoculation, PGRN -/mice exhibited increased macrophage recruitment in ME but delayed bacteria clearance. They found the production of CCL2 is increased, which could contribute to enhanced macrophage recruitment, whereas the delayed bacteria clearance is most likely due to impaired endocytosis capacity of macrophages (Wang et al, 2018).…”
Section: Genes Involved In Anti-inflammatory Responses In Ommentioning
confidence: 99%